Chondroclasts are mature osteoclasts which are capable of cartilage matrix resorption - Knowles, H; Moskovsky, L; Thompson, M; Grunhen, J; Cheng, X; Kashima, T; Athanasou, N (2012)
Multinucleated cells termed chondroclasts have been observed on the deep surface of resorbed hyaline cartilage but the relationship of these cells to macrophages and osteoclasts and their role in rheumatoid arthritis (RA) and other arthritic conditions is uncertain. Multinucleated cells in RA and other arthritic conditions showing evidence of cartilage resorption were characterised immunohistochemically for expression of macrophage/osteoclast markers. Mature human osteoclasts formed from circulating monocytes and tissue macrophages were cultured for up to 4 days on slices of human cartilage and glycosaminoglycan (GAG) release was measured. Multinucleated cells resorbing unmineralised cartilage were seen in osteoarthritis, RA, septic arthritis, avascular necrosis and in four cases of giant cell tumour of bone that had extended through the subchondral bone plate. Chondroclasts expressed an osteoclast-like phenotype (TRAP+, cathepsin K+, MMP9+, CD14-, HLADR-, CD45+, CD51+ and CD68+). Both macrophages and osteoclasts cultured on cartilage released GAG. These findings indicate that chondroclasts have an osteoclast-like phenotype and that mature human osteoclasts are capable of cartilage matrix resorption. Resorption of unmineralised subchondral cartilage by chondroclasts and macrophages can be a feature of joint destruction in inflammatory and non-inflammatory arthropathies as well as inflammatory and neoplastic subchondral bone lesions. © Springer-Verlag 2012.